2017
DOI: 10.1093/cercor/bhx275
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Activation of the Infralimbic Cortex Suppresses the Return of Appetitive Pavlovian-Conditioned Responding Following Extinction

Abstract: The infralimbic medial prefrontal cortex (IL) is important for suppressing learned behavior after extinction, but whether this function extends to responses acquired through appetitive Pavlovian conditioning is unclear. We trained male, Long-Evans rats to associate a white-noise conditional stimulus (CS; 10 s; 14 presentations per session) with 10% liquid sucrose (0.2 mL per CS presentation), and recorded entries into the fluid port during the CS. The CS was presented without sucrose in subsequent extinction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 41 publications
6
34
0
Order By: Relevance
“…With the rapid and widespread adoption of lightinducible technologies in neurobiology (Rost et al, 2017), these results provide a path forward when using these techniques in vitro. Recent reports have documented light-induced gene expression alterations of Fos in vivo (Villaruel et al, 2018), which may be the result of a similar stress response from poor heat dissipation during extended exposure times in vivo (Owen et al, 2019). In sum, our study highlights the importance of experimental design when using photoactivatable and imaging technologies.…”
Section: A B Csupporting
confidence: 60%
“…With the rapid and widespread adoption of lightinducible technologies in neurobiology (Rost et al, 2017), these results provide a path forward when using these techniques in vitro. Recent reports have documented light-induced gene expression alterations of Fos in vivo (Villaruel et al, 2018), which may be the result of a similar stress response from poor heat dissipation during extended exposure times in vivo (Owen et al, 2019). In sum, our study highlights the importance of experimental design when using photoactivatable and imaging technologies.…”
Section: A B Csupporting
confidence: 60%
“…Using this task, we previously reported selective ABA renewal of responding to an alcohol-predictive CS+ (Chaudhri et al, 2008b) that was dependent on dopaminergic (Sciascia et al, 2014) and cholinergic neurotransmission (Lacroix et al, 2017). We also reported ABA renewal of responding to a CS+ that predicted sucrose (Chaudhri et al, 2008b) and a reduction of this effect by optogenetic activation of the infralimbic prefrontal cortex during the CS (Villaruel et al, 2018). Given that ABA renewal is a reliable phenomenon across learning paradigms, we predicted that a return to the conditioning context following extinction in a different context would selectively renew CS+ responding in both alcohol-and sucrose-trained rats.…”
Section: Introductionmentioning
confidence: 89%
“…The function of IL is important for the expression of auditory-triggered conditioned fear in situations of latent inhibition. If IL is inhibited (e.g., infusion of GABAergic agonist, or activation of inhibitory M4 DREADD) the 'extinction' or outcome-specific inhibition disappears and the extinct behavior is reinstated (Do-Monte et al, 2015;Laurent et al, 2016) and if IL is stimulated (e.g., ChR2 or GABAergic antagonist) the extinction is strengthen (Do-Monte et al, 2015;Lingawi et al, 2018) and attenuation of responses to the conditioned stimulus is observed (Villaruel et al, 2018). Following a slightly different approach Halladay & Blair (2017) demonstrated that bilateral IL inactivation (GABAergic agonist) increases freezing responses and conditioned motor inhibition, whereas bilateral activation (GABAergic antagonist) enhances conditioned motor activation (turning away from an anticipated eyelid shock).…”
Section: Prelimbic (Prl) and Infralimbic (Il) Prefrontal Corticesmentioning
confidence: 99%